The Comparative Study Of Climatic Changes on the Breeding Performances of an Indian Catfish Heteropneustes Fossilis (Bloch) (International Journal of Food and Nutritional Sciences, 2024)
In the Indian catfish, or stinging catfish, Heteropneustes fossilis (Bloch), also referred to as shingi locally, is a widely cultivated commercial species. Because of its distinct flavor, high nutritional content, low fat level, high iron content, and therapeutic qualities, the species is regarded in Bengali tradition as a nutritional supplement for recovering patients. India has seen a sharp rise in the demand for stinging catfish cultivation; however the needs of commercial aquaculture farms cannot be met by natural or wild sources of fry. Furthermore, fish farmers have a poor opinion of the quality of stinging catfish fingerlings and fry raised in hatcheries. Climate change related effects include changes in physico-chemical proprieties of sea and freshwater, such as variations in water temperature, salinity, pH/pCO2 and oxygen content, which can impact fish critical physiological functions including reproduction. In this context, the main aim of the present review is to discuss how climate change related effects (variation in water temperature and salinity, increases in duration and frequency of hypoxia events, water acidification) would impact reproduction by affecting the neuroendocrine axis (brain-pituitary-gonad axis).